2004
DOI: 10.1007/s00170-003-1919-0
|View full text |Cite
|
Sign up to set email alerts
|

Workpiece representation for virtual turning

Abstract: In order to stay competitive with international markets, companies must deliver new products with higher quality in a shorter time with a broader variety of versions at minimum costs. Virtual manufacturing (VM) is quickly becoming an interesting strategy for product development. Primarily aimed at reducing the lead times to market and costs associated with new product development, VM offers a test-bed for the timeconsuming and expensive physical experimentation. In this paper, several key issues for developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The obvious benefit of simulation‐based training lies within the removal or reduction of the existing hazards through virtualisation or abstraction. The authors describe a specific avoidance of injuries [174], and avoidance of damage to equipment [38,78,85,112], damaging interference with other parts of the system [27,165] or general avoidance of risks and an increased safety [43,63,114,185].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obvious benefit of simulation‐based training lies within the removal or reduction of the existing hazards through virtualisation or abstraction. The authors describe a specific avoidance of injuries [174], and avoidance of damage to equipment [38,78,85,112], damaging interference with other parts of the system [27,165] or general avoidance of risks and an increased safety [43,63,114,185].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation‐based training can be used to decrease training costs [15,49,63,114,165,174,185]. The potential savings through simulation‐based training rise with the training costs within the original system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the geometrical model of virtual workpiece can be represented by its profile of half-axial cross-section. A successful representation of the virtual workpiece has been addressed by the present authors [18]. Rendering the virtual workpiece with full details of virtual machining is time consuming.…”
Section: Virtual Workpiecementioning
confidence: 99%
“…The fluctuation in cutting forces may result in vibration in the cutting system. The influence of vibration on the surface roughness and form accuracy of the machined surface has been previously discussed [18][19][20][21]. Most researchers found that the machined surface roughness in the infeed cutting direction is more dominant than it is in the main cutting direction, as the relative displacement of the tool in the main cutting direction does not engage in the generation of surface roughness [19].…”
Section: Dynamic Model For the Cutting Systemmentioning
confidence: 99%
“…In [29] some issues for developing a virtual turning lathe by using virtual manufacturing technology are discussed, i.e., representation of a workpiece capable of transferring error data used for machining accuracy prediction. A virtual machining and inspection system (VMIS) for ultra-precision diamond turning is also presented.…”
Section: Virtual Manufacturingmentioning
confidence: 99%